Training the Gastroenterologist of the Future: A Different Mix of Knowledge, Skills and Attitudes in Needed - Claude C Roy (Canadian Journal of Gastroenterology)
In the United States, the declining interest of residents in gastroenterology is thought to be the result of the specialty being too procedure driven and not intellectually challenging. It is clear that the growth of technology and excessive demands for procedures have forced the curtailing of clinic time, erosion of clinical skills, distraction from scholarly pursuits and a decrease in the intellectual content of our training programs. In order to attract the ’best and the brightest’ and to better prepare gastroenterologists for the future, trainees will require more knowledge and experience in nutrition, genetics and the evaluative sciences. Furthermore, they need to realize that the main responsibility of clinicians is problem solving. This can be learned only through personal clinical experience and teaching by clinicians with good analytical and intuitive skills. Quality care requires the integration of the needs, means and preferences of patients with evidence-based medical practice. Finally, new physicians should be imbued with the concept that an empathic relationship with patients is crucial for the accurate collection of information and plays an important therapeutic role.